Determination of cisplatin, transplatin and amminetri-chloroplatinate by high performance liquid chromatography in one run using 4-methyl-2-thiouracil as derivatizing agent - (:unkn) unknown (VIEWEG, 1999)
We have developed a simple, rapid, selective and sensitive method for detecting the antitumour agent cis-diamminedichloroplatinum (II) (cisplatin) (CDDP) and its toxic impurities trans-diamminedichloroplatinum (II) (transplatin) (TDDP) amminetri-chloroplatinat (ATCP) anion using HPLC in one run. By using 4-methyl-2-thiouracil (MTU) as a derivatizing agent, new compounds have been formed from the Pt compounds and separated on a mu-Bondapak C-18 column with isocratic elution and detection at 315 nm. Reactant concentration, methanol content, pH and the reaction time on yield of derivatives were investigated and the optimum conditions for the detection response were defined. The derivatives of each of the three platinum compounds formed in an acetate buffer solution containing 40 % (v/v) methanol and 0.9 % KCl solution at pH 3.7 and ambient temperature were only stable for one hour.
Keywords: column liquid chromatography; cis-diamminedichloroplatinum (II); transdiamminedichloroplatinum (II); amminetri-chloroplatinate; 4-methyl-2-thiouracil; PLATINUM(II) COMPLEXES; POSTCOLUMN DERIVATIZATION; PLASMA ULTRAFILTRATE; DIETHYLDITHIOCARBAMATE; URINE; ION; CIS-DICHLORODIAMMINEPLATINUM(II); SPECTROSCOPY; SULFUR